2012
DOI: 10.2298/tsci120503181v
|View full text |Cite
|
Sign up to set email alerts
|

Avoidable and unavoidable exergy destruction and exergoeconomic evaluation of the thermal processes in a real industrial plant

Abstract: Exergy analysis is a universal method for evaluating the rational use of energy. It can be applied to any kind of energy conversion system or chemical process. An exergy analysis identifies the location, the magnitude and the causes of thermodynamic inefficiencies and enhances understanding of the energy conversion processes in complex systems. Conventional exergy analyses pinpoint components and processes with high irreversibility. To overcome the limitations of the conventional analyses and to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…According to Vuckovic et al. [ 53 ], however, circulation pumps of a steam boiler have the greatest potential for improvement because the exergy destruction is avoidable in the steam boiler. The air compressor has a high exergy efficiency of 73.55%, when compared with the other utility equipment that work in line with the mixer, such as the NH 3 compressor (52.08%), treated H 2 O pump (0.63%), and syrup pump (0.83%).…”
Section: Resultsmentioning
confidence: 99%
“…According to Vuckovic et al. [ 53 ], however, circulation pumps of a steam boiler have the greatest potential for improvement because the exergy destruction is avoidable in the steam boiler. The air compressor has a high exergy efficiency of 73.55%, when compared with the other utility equipment that work in line with the mixer, such as the NH 3 compressor (52.08%), treated H 2 O pump (0.63%), and syrup pump (0.83%).…”
Section: Resultsmentioning
confidence: 99%
“…For evaluating the performance of a system from different viewpoints, it is necessary to perform the energy analysis of the whole system. The general forms of the mass and energy balance equations for a control volume at steady-state flow are expressed [27]:…”
Section: The Energy Analysis Of the Absorption Chiller Network Plantmentioning
confidence: 99%
“…A specific approach for assessing the opportunities for efficiency improvement of a real industrial plant is demonstrated in [12]. It includes both conventional and advanced exergy analyses and exergy-economic method and provides useful information about interactions among the components, revealing the real potential for improvement of the whole system and its components.…”
Section: Introductionmentioning
confidence: 99%